A league of their own: services exporters – a developing country perspective. Issue 5 (3rd July 2016) - Dincer, N. Nergiz; Tekin-Koru, Ayça
Abstract : This paper provides a firm-level portrait of services exporters along with goods exporters in a developing country. Current findings of firm-level services trade literature suggest that the stylized facts of goods trade apply to services trade as well for a set of developed countries. This paper investigates if similar results hold for a developing country, Turkey, for the period 2003–2008. Most results lend support to the evidence found in the previous literature. However, the analysis of Turkish data shows that firms that export both goods and services are larger than those exporting goods or services only while multinationals that sell only goods are bigger than multinationals exporting both goods and services or those exporting only services.